HIST1H1B Promotes Basal-Like Breast Cancer Progression by Modulating CSF2 Expression - Liao, Ruocen; Chen, Xingyu; Cao, Qianhua; Wang, Yifan; Miao, Zhaorui; Lei, Xingyu; Jiang, Qianjin; Chen, Jie; Wu, Xuebiao; Li, Xiaoli; Li, Jun; Dong, Chenfang (Frontiers in Oncology, 2021)
Basal-like breast cancer (BLBC) associates with a poor clinical outcome; however, the mechanism of BLBC aggressiveness remains unclear. Here, we show that the linker histone HIST1H1B is dramatically elevated in BLBC due to HIST1H1B copy number amplification and promoter hypomethylation. HIST1H1B upregulates colony-stimulating factor 2 (CSF2) expression by binding the CSF2 promoter. HIST1H1B expression promotes, whereas knockdown of HIST1H1B expression suppresses tumorigenicity. In breast cancer patients, HIST1H1B expression is positively correlated with large tumor size, high grade, metastasis and poor survival. Our study contributes to an understanding of how HIST1H1B promotes BLBC progression, providing a potential prognostic marker and therapeutic target for this disease.